Decision aids to improve informed decision‐making in pregnancy care: a systematic review. Issue 3 (12th November 2012) - Vlemmix, F; Warendorf, JK; Rosman, AN; Kok, M; Mol, BWJ; Morris, JM; Nassar, N
<x xml:space="preserve">Abstract</x> Background Rapid development in health care has resulted in an increasing number of screening and treatment options. Consequently, there is an urgency to provide people with relevant information about benefits and risks of healthcare options in an unbiased way. Decision aids help people to make decisions by providing unbiased non‐directive research evidence about all treatment options. Objective To determine the effectiveness of decision aids to improve informed decision making in pregnancy care. Search strategy We searched MEDLINE (1953–2011), EMBASE (1980–2011), CENTRAL (CENTRAL, the Cochrane Library; 2011, Issue 4), Psycinfo (1806–2011) and Research Registers of ongoing trials (www.clinicaltrials.gov, www.controlled-trials.com). Selection criteria We included randomised controlled trials comparing decision aids in addition to standard care. The study population needed to be pregnant women making actual decisions concerning their pregnancy. Data collection and analysis Two independent researchers extracted data on quality of the randomised controlled trial (GRADE criteria), quality of the decision aid (IPDAS criteria), and outcome measures. Data analysis was undertaken by assessing group differences at first follow up after the interventions. Main results Ten randomised controlled trials could be included. Pooled analyses showed that decision aids significantly increased knowledge, (weighted mean difference 11.06, 95% confidence interval 4.85–17.27), decreased decisional conflict scores (weighted mean difference −3.66, 95% confidence interval −6.65 to −0.68) and decreased anxiety (weighted mean difference −1.56, 95% confidence interval −2.75 to −0.43). Conclusions Our systematic review showed the positive effect of decision aids on informed decision making in pregnancy care. Future studies should focus on increasing the uptake of decision aids in clinical practice by identifying barriers and facilitators to implementation.